Saddle Pulmonary Embolism with Thrombus in Transit across a Patent Foramen Ovale - Fitzgerald Shepherd; Ashley White-Stern; Oloruntobi Rahaman; Damian Kurian; Karen Simon (Case Reports in Cardiology)
This is the case of a 25-year-old obese man who presented with acute shortness of breath, chest pain, and palpitations. Of note, he lives a sedentary lifestyle and was recently hospitalized for incision and drainage of a left foot abscess. On presentation he was tachypnoeic, tachycardiac, and hypoxic but blood pressure was stable. Laboratory studies were significant for elevated D-dimer and mildly increased troponin. On further investigation he was found to have a saddle pulmonary embolism with massive clot burden. Echocardiogram revealed thrombus in transit and McConnell’s sign. He underwent surgical embolectomy and closure of a patent foramen ovale. This is a particularly rare case, especially in such a young patient. Because this is a rare diagnosis, with insufficient data, there is no formally established treatment guideline. However, in patients who are good surgical candidates, studies have shown better outcome with surgical embolectomy as compared to anticoagulation alone or thrombolysis.